ENVIRONMENTAL CRISIS AND RELIGIONS - Kalapura, Jose (Journal of Dharma, 2006)
There is a close linkage between ecology and religions.1 The crisis in our ecosystem endangering the life of humans and other living beings is one of the most frightening problems of the present time. This crisis is very much a religious and spiritual issue and demands a befitting response through scientific outlook and religious approach.2 Creating a healthy and wholesome environment involves restoring the innate health of the cosmos that has been tarnished because of various causes.